Spectroscopic investigations and physico-chemical characterization of newly synthesized mixed-ligand complexes of 2-methylbenzimidazole with metal ions - Shaker, S.A.; Ali, Hapipah Mohd; Khaledi, H. (2011)
Some mixed ligand complexes containing 2-methylbenzimidazole and thiocyanate ion were synthesized. Free ligands and their metal complexes were characterized using elemental analysis, determination of metal, magnetic susceptibility, molar conductivity, infrared, UV-VIS, and (H-1, C-13) NMR spectra, and X-ray structure analysis. The results suggest that the Ag(I) complex has linear geometry, Fe(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) have tetrahedral geometry, Pd(II) complex has square planar geometry, VO(IV) square pyramidal geometry, Pb(II) irregular tetrahedral geometry, and that the Cr(III) and Mn(II) complexes have octahedral geometry. The following general formulae were proposed for the prepared complexes: [AgBX], [CrB3X3], (HB)(2)[MnB2X4] center dot 2B and [MB2X2], where B = 2-methylbenzimidazole, HB = 2-methylbenzimidazolium, X = thiocyanate ion, and M = VO(IV), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), Pd(II), Cd(II), and Pb(II). Molar conductance of a 10(-3) M solution in N,N-dimethyl formamide (DMF) indicates that all the complexes are non-electrolytes except the Mn(II) complex which is an electrolyte because the molar conductivity of its solution in DMF is high.